2019
DOI: 10.1016/j.apcata.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol conversion into 1,3-butadiene over a mixed Hf-Zn catalyst: A study of the reaction pathway and catalyst deactivation

Abstract: Some fundamental and practical aspects of a Hf-Zn catalyst, with a nominal composition of 3.0 wt% Hf and 9.3 wt% Zn and prepared as a physical mixture of Hf/SiO2 (85 wt%) and the zincsilicate hemimorphite (15 wt%), have been studied for the one-step conversion of ethanol to 1,3butadiene. The elucidation of the main reactions leading to 1,3-butadiene and by-products was made by means of kinetic curves and catalytic tests where intermediates were individually fed. In addition, the convenience of by-product separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 59 publications
4
56
0
Order By: Relevance
“…In fact, the necessity of basic or redox sites for converting ethanol first to acetaldehyde before BD has often been highlighted. 33,36,90 However, in our previous publication, we reported that CO 2 -TPD of Zn and Tacontaining catalysts revealed little correlation between the basic properties of our samples and their performances; 37 the inadequacy of CO 2 for probing sites active in the Lebedev process reported by other scholars may be the cause. 77,91 H 2 -TPR was also used to characterize the properties of catalysts capable of dehydrogenation reactions, as their reducibility can be related to activity.…”
Section: Chemical Propertiesmentioning
confidence: 52%
See 4 more Smart Citations
“…In fact, the necessity of basic or redox sites for converting ethanol first to acetaldehyde before BD has often been highlighted. 33,36,90 However, in our previous publication, we reported that CO 2 -TPD of Zn and Tacontaining catalysts revealed little correlation between the basic properties of our samples and their performances; 37 the inadequacy of CO 2 for probing sites active in the Lebedev process reported by other scholars may be the cause. 77,91 H 2 -TPR was also used to characterize the properties of catalysts capable of dehydrogenation reactions, as their reducibility can be related to activity.…”
Section: Chemical Propertiesmentioning
confidence: 52%
“…Interestingly, we did not observe the passivation of stronger acid sites caused by the presence of Zn as reported by other scholars on Zn-Hf and Zn-Zr catalysts. 28,36,81 Instead, the Zn-TUD-1 possessed more strong sites than Ta-TUD-1. The significantly different preparation methods used may explain this discrepancy, as other works have generally added Zn subsequently.…”
Section: Chemical Propertiesmentioning
confidence: 93%
See 3 more Smart Citations